Mimicry, Hybridity and Liminality in The Movie Avatar: The Way of Water (A Postcolonial Study) - Andreas, Rino; Sanjaya, Candra Rahmat; Wihastiningrum, Zabrina Damayanti; Putra, Romi Iriandi (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2023)
Film is a medium that describes the relationship between "Western" and "Eastern" cultures. This study aims to examine the discourse of postcolonialism in the movie Avatar: The Way of Water (2022) from the perspective of Homi K. Bhabha regarding mimicry, hybridity and liminality. This qualitative research uses a content analysis method. As a result, the film Avatar displays a film plot that positions the people of Navi as an "eastern" group colonized by military forces from the "West". The characters in the film, namely Jake Sully and his family, are not trapped in the dichotomy between the colonizers and the colonized, but form and create a hybrid identity between humans and sailors. Thus the relationship between the characters in the movie Avatar is in the "space between" which is growing. a reading of postcolonialism in film.